THE WORKS OF T.A. JDANKO ON THE STUDY OF THE TOPONYMY OF THE KARAKALPAK PEOPLE (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article is dedicated to the works of the ethnographer T.A. Zhdanko on the Karakalpaks, their clans, and toponymy.